The Relationship Between Perceived Organisational Support and Employee WellBeing Among Employees of PT X in Semarang - Rangga Nibras Aufa; Aldani Putri Wijayanti (Journal of Social and Industrial Psychology, 2025)
Employees are a valuable asset for a company and contribute to the achievement of its goals. The purpose of this study is to identify the relationship between perceived organisational support and employee well-being among employees. This research employed a quantitative method, using proportionate sampling to ensure that each subgroup of the population was represented in the sample. Participants were employees with a minimum tenure of three months across various divisions, drawn from a total population of 847 employees. The study involved constructing a perceived organisational support scale with 28 items (α = 0.920) and adopting an employee well-being scale with 18 items (α = 0.827). Data were collected from 266 respondents; Spearman’s rho was 0.147 with a significance of 0.008 (p < 0.05). The results indicate a weak but significant positive correlation between perceived organisational support and employee well-being, suggesting that higher perceived support is associated with a slight increase in employee well-being.